IMF Drawing Programs : Participation Determinants and Forecasting - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2007)
This paper studies the factors that have influenced countries' participation in IMF drawing programs. IMF drawing programs are defined as the period of a Stand-By Arrangement or an Extended Fund Facilities program during which a country borrows from the Fund. Since this definition excludes precautionary arrangements and periods during which the program went off-track, it provides a closer link to the factors that have influenced the evolution of IMF credit outstanding. The analysis uses quarterly data during the period 1982-2005 and focuses on developing, non-PRGF eligible countries. Country-specific variables-net international reserves and GDP growth-together with a global factor-world GDP growth-are found to be among the most significant determinants of countries' participation in IMF drawing programs. The importance of the global factor is not uniform during the period reviewed. The influence of world GDP growth seems to have been significant during the 1980s debt crises but not since the Mexican crisis in 1994. An out-of-sample forecast evaluation of the period 2004-5 reveals that the model has some predictive power.